Manganese-doped nanotheranostic system for MRI-guided photothermal therapy of malignant pleural mesothelioma: in vivo study - Lei, Lichang; Zi, Hongjiao; Kang, ShaoLei; Duan, Hui; Zhang, Zhenghua; Gao, Chao; Xu, Ruoyun; Han, Dan (Frontiers in Chemistry, 2025)
IntroductionMagnetic Resonance Imaging (MRI)-guided photothermal therapy (PTT) holds significant promise for the treatment of solid tumors, however, its diagnostic and therapeutic efficacy in malignant pleural mesothelioma (MPM) remains underexplored. To address the limitations of traditional gadolinium (Gd)-based MRI contrast agents, such as intolerance in patients with renal insufficiency and T1 signal attenuation at high field strengths, as well as oxidative stress damage caused by manganese ion leakage from manganese-based materials, this study aims to develop highly chelated and stable manganese polydopamine (Mn-PDA) multifunctional nanoprobes for MRI monitoring and PTT treatment of MPM.MethodsMn2+ and dopamine were chelated into Mn-PDA NP nanospheres in an ethanol-water system. The physicochemical properties were characterized using Transmission Electron Microscopy (TEM), Dynamic Light Scattering (DLS), zeta potential, Fourier Transform Infrared Spectroscopy (FT-IR), X-ray Photoelectron Spectroscopy (XPS), and Electron Paramagnetic Resonance (EPR). The photothermal performance under 808 nm laser irradiation was also evaluated. The MRI imaging performance (longitudinal/transverse relaxation rates, r1/r2) and manganese ion deposition quantification of Mn-PDA NPs were evaluated in vitro and in vivo at 3.0 T MR scanner. Additionally, the PTT efficacy of Mn-PDA NPs was evaluated in MSTO-211H cells and xenograft tumor models. Biocompatibility was assessed through H&E staining of major organs and blood biochemical analyses.ResultsMn-PDA NPs exhibited a spherical morphology with uniform size ( 200 nm), along with high photothermal conversion efficiency, favorable T1-weighted MRI contrast enhancement and low cytotoxicity. At 8 hours post-injection in vivo, Mn-PDA NPs resulted in a 42.9% enhancement in T1-weighted MRI signals within MPM tumors, accompanied by specific tumor accumulation. Under 808 nm laser irradiation, Mn-PDA NPs inhibited MPM tumor growth, as evidenced by reduced tumor volume, expanded areas of tumor necrosis (H&E staining), and downregulated Ki-67 expression. Moreover, stable body weight, normal histological features of major organs, and unaltered blood biochemical parameters were observed in the animals.DiscussionThese findings indicate that Mn-PDA NPs are effective dual-functional agents, serving as both MRI contrast agents and photothermal therapeutics. They exhibit good tumor targeting ability, excellent imaging performance, potent therapeutic efficacy, and high biosafety, thereby offering a promising therapeutic strategy for MPM management.